Fumigation and repellency of essential oils against Callosobruchus maculatus (Coleoptera: Chrysomelidae: Bruchinae) in cowpea - Oliveira, José Vargas de; França, Solange Maria de; Barbosa, Douglas Rafael e Silva; Dutra, Kamilla de Andrade; Araujo, Alice Maria Nascimento de; Navarro, Daniela Maria do Amaral Ferraz (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to assess the fumigant and repellent effects of essential oils on adults of Callosobruchus maculatus and to identify the chemical composition of two of the tested essential oils. For the fumigation test, the oils of Schinus terebinthifolius, Piper aduncum, Syzygium aromaticum, Piper hispidinervum, Cymbopogon citratus, Cinnamomum zeylanicum, and the eugenol compound were tested at different concentrations on C. maculatus adults. For the repellency test, the oils of S. terebinthifolius, P. aduncum, P. hispidinervum, S. aromaticum, Jatropha curcas, and Ricinus communis were evaluated. In the fumigation test, it was observed that P. aduncum and eugenol showed the highest and lowest LC50s, of 169.50 and 0.28 µL L-1 air, respectively. In the repellency test, the oils of S. aromaticum and P. hispidinervum were repellent to C. maculatus. Gas chromatography coupled to mass spectrometry (GC-MS) analysis of these two oils identified 42 compounds, of which safrole was the main component of P. hispidinervum and eugenol of S. aromaticum. The essential oils of S. aromaticum, C. zeylanicum, and the eugenol compound are the most promising to control C. maculatus, via fumigation.